Initial immunological changes as predictors for house dust mite immunotherapy response. Issue 10 (15th September 2015) - Gómez, E.; Fernández, T. D.; Doña, I.; Rondon, C.; Campo, P.; Gomez, F.; Salas, M.; Gonzalez, M.; Perkins, J. R.; Palomares, F.; Blanca, M.; Torres, M. J.; et al.
Summary: Background: Although specific immunotherapy is the only aetiological treatment for allergic disorders, the underlying mechanisms are not fully understood. Specific immunotherapy induces changes in lymphocyte Th subsets from Th2 to Th1/Treg. Whether differences in immunological patterns underlie patient response to immunotherapy has not yet been established. Objectives: We studied the immunological changes occurring during a 1‐year period of Dermatophagoides pteronyssinus (DP) immunotherapy and their relation with clinical outcome. Methods: We included 34 patients with DP allergy who received subcutaneous specific immunotherapy (SCIT) for 1 year. Following treatment, patients were classified as responders or non‐responders. Fourteen allergic subjects who did not receive SCIT were included as controls. Peripheral blood was obtained at 0, 1, 3, 6 and 12 months and cultured with nDer p 1. Phenotypic changes, cytokine production and basophil response were analysed by flow cytometry; transcription factors were measured by mRNA quantification. Serum immunoglobulin levels were also measured. Results: After 1 year of SCIT, 82% of cases showed improved symptoms (responders). Although increases in sIgG4 were observed, BAT reactivity was not modified in these patients. Increases in T‐BET/FOXP3 as well as nDer p 1‐specific Th1/Treg frequencies were also observed, along with a decrease in Th2, Th9 and Th17. These changes corresponded to changes in cytokine levels. Conclusion: Patients who respond well to DP‐SCIT show immunological differences compared to non‐responders. In responders, basal differences include a lower frequency of Th1 and higher frequencies of Th2, Th9 and Th17 cells. After 1 year of treatment, an increased production of sIgG4 was observed in responders, along with a change in Th2 response towards Th1/Treg.